The Best Leadership Styles for Preventing the Educational Crisis - Abdallah, Asma; Alkhrabsheh, Abdullah (Opción, 2019)
The purpose of our research is to find out the relationship between leadership styles and the quality of higher education and to determine the most effective leadership style for preventing the educational crisis. In this research, the used correlation methods and a survey in the form of a questionnaire. The results of the study showed a positive correlation between leadership styles and the quality of education (p <0.01, sig = 0.000). In conclusion, the transformational leadership style is the most effective among the existing leadership styles for preventing the educational crisis.